Formation of Highly Conductive Boron-Doped Diamond on TiO2 Nanotubes Composite for Supercapacitor or Energy Storage Devices. Issue 10 (1st January 2015) - Sawczak, M.; Sobaszek, M.; Siuzdak, K.; Ryl, J.; Bogdanowicz, R.; Darowicki, K.; Gazda, M.; Cenian, A.
Abstract : In the present paper, we report the phenomena of the formation of the novel composite nanostructures based on TiO2 nanotubes (NTs) over-grown by thin boron-doped diamond (BDD) film produced in Microwave Plasma Enhanced Chemical Vapor Deposition (PE MWCVD). The TiO2 nanotube array overgrown by boron-doped diamond immersed in 0.1 M NaNO3 can deliver high specific capacitance of 7.46 mF cm −2 . The composite electrodes were characterized by scanning electron microscopy (SEM), Raman spectroscopy, X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) techniques. The depth-resolved investigations reveal that the primary anatase structure of TiO2 NTs was partially transformed into Ti2 O3 and non-stoichiometric TiC fractions. The explanation for this effect is the decomposing of TiO2 NTs in the presence of activated hydrogen and carbon in the plasma leading to enhanced dehydration of NTs and carbon bonding originating from dissociated methane. This phenomena description fits also to processes demonstrated at hydrogenated TiO2 (H-TiO2 ) nanotube arrays used as electrode material for supercapacitors. Nevertheless, the increase of electrochemical performance can be attributed to several reasons: (1) the unique morphology of titania nanotubes and columnar BDD with intergrain defects and valley increasing specific area of electrode and (2) presence of TiC and Ti2 O3 fractions introducing additional capacitance.